Kadar Kolesterol Daging Pada Keturunan F1 Dari Induk Puyuh Jepang (Coturnix coturnix japonica L.) Yang Diberi Suplemen Tepung Kunyit (Curcuma longa L.) Dalam Pakan - Andriani, Regita; Saraswati, Tyas Rini; Tana, Silvana (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2018)
Quail is one of poultry commodities that compliance the needed of animal protein like egg and meat. Good quality was breed from quail parent that has good physiological condition. This research aimed to quantified cholesterol of quail meat from F1 from quail parent that treatment using turmeric powder supplement on itsfed in order to obtained best quail chick with good physiological condition. This research use Completely Randomized Design (CRD) experimental method. Animal on this research was 15 Japanese quail (Coturnix coturnix japonica L.) hens that gave 3 treatments with 5 repetitions. K0 was F1 of quail parent without turmeric powder supplementation, K1 was F1 of quail parent with 54 mg/quail/day turmeric powder supplementation before its sex period, K2 was F1 of quail parent with 108 mg/quail/day turmeric powder supplementation before its sex period. The F1 quail was fed using standard quail feed. Data was obtained from daily fed consumption average, daily water consumption, and quail meat cholesterol rate on 60 day old chicken. Data was analyses using Analysis of Variance (ANOVA). This research result showed that daily fed consumption, daily water consumption and meat cholesterol rate of F1 that treatment using turmeric powder supplementation wasnâ€™t show significant difference, so conclusion of this research is physiological condition of F1 was normal.Â Key words: Quail Meat Cholesterol, F1 of Japanese quail (Coturnix coturnix japonica), Turmeric powder